Preventing problem behaviors : schoolwide programs and classroom practices - Algozzine, Robert; Daunic, Ann P.; Smith, Stephen W., 1952- (Corwin, 2010)
This research-based guide offers specific strategies and plans for preventing problem behavior at both the classroom and school level.
Keywords: problémové děti; školní didaktika; problem children; classroom management; elektronické knihy; příručky; electronic books; handbooks and manuals